Microstructural investigation of FeCrNbB amorphous/nanocrystalline coating produced by HVOF. (5th December 2016) - Guo, Y.; Koga, G.Y.; Jorge, A. Moreira; Savoie, S.; Schulz, R.; Kiminami, C.S.; Bolfarini, C.; Botta, W.J.
Abstract: Protective coatings of the steel tubes used in the oil and petrochemical industry require good corrosion and wear resistance. Our previous research shows that the FeCrNbB quaternary system is a promising candidate for the above application. In the current work, a new FeCrNbB glassy alloy, with nominal composition Fe57 Cr9 Nb13 B21, was used to produce amorphous/nanocrystalline coatings by High-Velocity Oxygen Fuel (HVOF) thermal spray process onto 410 stainless steel substrate. The composition was designed to induce, during coating production, preferential formation of fine Nb-rich phases embedded within an amorphous matrix. Amorphous broad halo as well as crystalline (Fe, Cr)NbB and (Fe, Cr, Nb)3 B2 peaks were confirmed by X-Ray diffraction (XRD) patterns and fine micrometric Nb-rich phases with the size ranging from about 1 μm to 100 nm were observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Large fraction of Nb-rich nanocrystals was revealed by high-angle annular dark field (HAADF) and elemental mapping. Some α-Fe, FeB and Fe2 B nanoparticles were also detected by XRD and TEM analyses. Due to the composite structure, the coating was found to exhibit much better wear resistance and higher hardness than the 410 stainless steel substrate. Graphical abstract: Highlights: A new Fe57 Cr9 Nb13 B21 amorphous/nanocrystalline coating was designed and obtained by HVOF thermal spray. The microstructure of the HVOF coating was investigated in details to identify the crystalline phases. Orientation image mapping was performed by TEM coupled with an ASTAR system to index the nanocrystalline phases. The coating exhibits high microhardness and good wear resistance due to the composite structure of amorphous and nanocrystalline phases.